THE RELATIONSHIP OF PROLONGED SITTING DUE TO ONLINE LEARNING TO MUSCULOSKELETAL DISORDERS (MSDS) IN MUHAMMADIYAH SMA STUDENTS, PALEMBANG CITY - juliastuti juliastuti juliastuti; Yudiansyah Yudiansyah (Masker Medika, 2022)
Introduction : Prolonged sitting is a sedentary activity for a long time characterized by low energy consumption in combination with movements in a sitting or lying position. Online learning can be one of the causes of this condition because during learning, students sit for about two-thirds of working hours and their sitting period usually lasts at least 30 minutes. Objective : This study aims to determine the relationship between prolonged sitting and musculosceletal disorders (MSDs) in Muhammadiyah high school students in Palembang. Methods: This type of research is a survey with a descriptive quantitative approach, using a Cross Sectional analytic method. Collecting data through the distribution of jotform questionnaires to students of SMA Muhammadiyah Palembang City. Results: Hypothesis test results obtained p value = 0.005, it can be concluded that there is a difference in the proportion of events between prolonged sitting and musculoskeletal disorders (MSDs). Conclusion: the results of this study found a relationship between prolonged sitting due to online learning and the occurrence of musculoskeletal disorders (MSDs). This research recommendation can be continued with research using a more specific MSDs measurement instrument